2014
DOI: 10.3325/cmj.2014.55.647
|View full text |Cite
|
Sign up to set email alerts
|

North vs south differences in acute peptic ulcer hemorrhage in Croatia: hospitalization incidence trends, clinical features, and 30-day case fatality

Abstract: AimTo assess the seven-year trends of hospitalization incidence due to acute peptic ulcer hemorrhage (APUH) and associated risk factors, and examine the differences in these trends between two regions in Croatia.MethodsThe study collected sociodemographic, clinical, and endoscopic data on 2204 patients with endoscopically confirmed APUH who were admitted to the Clinical Hospital Center “Sestre Milosrdnice,” Zagreb and Clinical Hospital Center Split between January 1, 2005 and December 31, 2011. We determined h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For the needs of this study, we treated Pelješac peninsula equally as islands since it is an equally isolated remote area. The two southernmost counties were used as the mainland controls, because previous studies suggested different health-related behaviors and outcomes in the coastal and continental Croatia ( 13 , 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the needs of this study, we treated Pelješac peninsula equally as islands since it is an equally isolated remote area. The two southernmost counties were used as the mainland controls, because previous studies suggested different health-related behaviors and outcomes in the coastal and continental Croatia ( 13 , 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…A second review article also from Brazil concluded that PU had not declined over the past decade, the percentage of patients with ulcers without H. pylori or NSAID intake, however, had increased in some centers to more than 50%, and H. pylori was only one factor in the genesis of PUD which now had a multifactorial etiology. Two articles, one from Canada and the other from Croatia , reviewed the incidence of PU hemorrhage. Both showed little change in incidence of DU bleeds, but GU bleeds had increased, mortality was unchanged the age of patients had risen, and NSAID intake had also increased.…”
Section: Peptic Ulcer Diseasementioning
confidence: 99%